2020
DOI: 10.1055/s-0040-1712121
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for High-Risk Pregnancies in the Setting of the COVID-19 Pandemic

Abstract: As New York City became an international epicenter of the novel coronavirus disease 2020 (COVID-19) pandemic, telehealth was rapidly integrated into prenatal care at Columbia University Irving Medical Center, an academic hospital system in Manhattan. Goals of implementation were to consolidate in-person prenatal screening, surveillance, and examinations into fewer in-person visits while maintaining patient access to ongoing antenatal care and subspecialty consultations via telehealth virtual visits. The ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
180
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(215 citation statements)
references
References 13 publications
1
180
0
11
Order By: Relevance
“…Several studies have not shown worse outcomes, even for women at high risk. 3,4 However, reliance on telehealth for prenatal care excludes people impacted by the "digital divide"-inequitable access to or use of remote communications technologies-such as those living in certain areas with low Internet connectivity, those who are poor and have no access to the hardware necessary for such visits (tablets, laptops, or computers), and those with poor technical literacy. 5 Restrictions against a companion being present during labor and delivery were widespread at the outset of the pandemic, depriving women of an option that has been shown to not only improve the childbirth experience and outcomes, but also prevent other forms of mistreatment during childbirth.…”
Section: Recent Changes To Maternity Carementioning
confidence: 99%
“…Several studies have not shown worse outcomes, even for women at high risk. 3,4 However, reliance on telehealth for prenatal care excludes people impacted by the "digital divide"-inequitable access to or use of remote communications technologies-such as those living in certain areas with low Internet connectivity, those who are poor and have no access to the hardware necessary for such visits (tablets, laptops, or computers), and those with poor technical literacy. 5 Restrictions against a companion being present during labor and delivery were widespread at the outset of the pandemic, depriving women of an option that has been shown to not only improve the childbirth experience and outcomes, but also prevent other forms of mistreatment during childbirth.…”
Section: Recent Changes To Maternity Carementioning
confidence: 99%
“…During the COVID-19 pandemic, prenatal and psychological services have been rapidly changing from face-to-face to online (Aziz et al, 2020;Zhou et al, 2020). For example, two hospitals and an affiliated clinic in New York City offered telehealth prenatal appointments during the COVID-19 outbreak.…”
Section: What Are the Good Psychological Practices In Perinatalmentioning
confidence: 99%
“…Regarding mental health support, they proposed a prior in-person session before starting the telehealth to ensure clinician-patient alliance. If there were specific concerns about domestic violence or any abusive relationship in the home environment, these issues would be discussed in this initial session as well (Aziz et al, 2020). Additionally, access to psychosocial support groups should be provided, even as an online service.…”
Section: What Are the Good Psychological Practices In Perinatalmentioning
confidence: 99%
“…Physical visits to the diabetes care team can be timed along with visits to the obstetrician and ultrasounds. [91][92][93][94] Oral glucose tolerance test (OGTT) at 24 to 28 weeks remains the gold standard for detecting gestational diabetes mellitus (GDM). However, as this would require repeated phlebotomy and more time spent at the specimen collection center, many experts have argued that this would increase the women's risk of acquiring COVID-19 infection.…”
Section: Endocrinology Endocrine Diseases In Women and Covid-19 Infecmentioning
confidence: 99%